Voting with your feet: Migration flows and happiness - Helena Marques; Gabriel Pino; J. D. Tena (SERIEs - Journal of the Spanish Economic Association, 2018)
We establish a nexus between migration flows and self-assessed happiness by proposing an empirical model that brings together the determinants of happiness proposed by psychology and the typical gravity variables from the economic migration literature. Taking this estimation net of the usual gravity controls we propose an alternative happiness index that is consistent with the revealed preferences about happiness determinants in countries with different development levels and institutions. The revelation of preferences is indicated by the estimated coefficients for each of the determinants of happiness such that their weights in the proposed migration-based index directly result from observed data. Finally, we compare the country classification suggested by our proposed index and two existing indexes based on self-assessed happiness, and analyse the sources of existing mismatches, with policy implications.
Keywords: F22; D60; C23; 330; Happiness; Subjective wellbeing; Revealed preferences; Migration; Gravity models; FEVD